PERCEIVED EFFECTIVENESS OF INFORMATION SOURCES IN MEETING INFORMATION NEEDS OF RICE GROWERS IN NEPAL - Prakash Baral (Agricultural Socio-Economics Journal, 2020)
A study was done to assess the effectiveness of different information sources in meeting information needs and utilization behavior of rice growers in western midhills of Nepal, taking 101 sample households. Survey design with a structured questionnaire was used for data collection under the pragmatic paradigm of social research. The study showed that 30 percent of farmers were high information seekers while about 59 percent were utilizing information highly implying that most farmers were using the information highly though they don't seek information by themselves. Input management and climatic information were highly sought and utilized. Though fellow and contact farmers were the more used source of information, however, respondents felt that extension personnel and agro-vets were more credible.  An assessment of the effective index showed that fellow farmers were highly effective followed by extension personnel and agro-vets while social media and ICTs were least effective. There was a significant positive correlation between information variables and education, ethnicity, number of crops grown and accessibility to information sources. However, poor accessibility of farmers to these sources was a major problem. Thus, a suitable information delivery system accessible to most farmers according to their time and needs should be designed regarding rice cultivation.